2004
DOI: 10.7863/jum.2004.23.12.1569
|View full text |Cite
|
Sign up to set email alerts
|

Bioeffects of Low-Frequency Ultrasonic Gene Delivery and Safety on Cell Membrane Permeability Control

Abstract: Objective. To develop a novel method of ultrasonic naked gene delivery (UNGD); to examine the relationship between optimal parameters of ultrasound exposure and cell membrane permeability, enzymes, and free radicals; and to find optimal control parameters that were realizable, reliable, and noncytotoxic for use in gene therapy. Methods. Suspensions of chicken, rabbit, and rat red blood cells and S180 cells were exposed to a calibrated ultrasonic field with different parameters in both the still and flowing sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 18 publications
0
19
0
1
Order By: Relevance
“…The results of [7] have shown that low frequency ultrasound , with intensities (most likely I SATA , spatial average temporal average intensity) between 0.2 W/cm 2 and 2.7 W/cm 2 , could be used to increase skin permeability. The outcome presented in [11] suggested that ultrasound of 35.1 kHz applied at pressure amplitudes between 67.1 kPa and 102.5 kPa could be effective in ultrasonic naked gene delivery while maintaining 90% cell viability. The experimental results published recently by the team of the University of Vermont suggested that sonoporation at 2 MHz carried out at 10% duty cycle and 80 W/cm 2 , spatial-peak, pulse-average (I sppa ) intensity could be successful in targeted drug delivery [12].…”
Section: Introductionmentioning
confidence: 93%
“…The results of [7] have shown that low frequency ultrasound , with intensities (most likely I SATA , spatial average temporal average intensity) between 0.2 W/cm 2 and 2.7 W/cm 2 , could be used to increase skin permeability. The outcome presented in [11] suggested that ultrasound of 35.1 kHz applied at pressure amplitudes between 67.1 kPa and 102.5 kPa could be effective in ultrasonic naked gene delivery while maintaining 90% cell viability. The experimental results published recently by the team of the University of Vermont suggested that sonoporation at 2 MHz carried out at 10% duty cycle and 80 W/cm 2 , spatial-peak, pulse-average (I sppa ) intensity could be successful in targeted drug delivery [12].…”
Section: Introductionmentioning
confidence: 93%
“…40,44,45 More controversial is the potential role of extra and/or intracellular free radical production produced during transient cavitation. 25,46,47 We have reported that the presence of free radical scavengers in the transfection medium has no effect on transgene expression following UEGT, suggesting that free radicals are not required for sonoporation. 46 In contrast, Juffermans et al 25 found that scavenging hydrogen peroxide (H 2 O 2 ) with extracellular catalase largely prevented the increased calcium permeability induced by low MI (0.1-0.5) ultrasound (1-3.6 MHz) in H9c2 rat cardiomyoblast cells.…”
Section: Multiple Biophysical Effects Of Ultrasound May Contribute Tomentioning
confidence: 99%
“…These high frequency vibrations have proved to be a useful, noninvasive method by which genetic therapeutics can be delivered both in vivo and in vitro. [1][2][3][4][5][6] This approach has successfully been used to aerosolize complexed DNA for topical delivery to the lungs. 7,8 Additionally, ultrasound has been employed to increase cell membrane permeability which has resulted in an enhancement in transfection efficiency.…”
Section: Introductionmentioning
confidence: 99%